2012
DOI: 10.1111/j.1600-0609.2011.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

BIRC6/Apollon gene expression in childhood acute leukemia: impact on therapeutic response and prognosis

Abstract: This is the first report to study BIRC6 gene in pediatric ALL. Our results suggested that BIRC6 gene expression could be considered as an adverse risk factor in childhood acute leukemia and, hence, could be used to guide therapeutic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 49 publications
10
29
0
Order By: Relevance
“…Carter et al [10] did not find any prognostic significance for Survivin or XIAP expression in adult AML samples, whereas BIRC6 overexpression is associated with unfavorable clinical features and negatively impacts on the 3-year relapse-free survival in childhood acute myeloid leukemia (AML) [11]. Similar results were obtained by Ismail et al in childhood AML and acute lymphoblastic leukemia (ALL) [12]. Abe et al [13] found lower expression of BIRC6 in bone marrow-derived cells of healthy donors compared to de novo AML samples.…”
Section: Introductionmentioning
confidence: 70%
“…Carter et al [10] did not find any prognostic significance for Survivin or XIAP expression in adult AML samples, whereas BIRC6 overexpression is associated with unfavorable clinical features and negatively impacts on the 3-year relapse-free survival in childhood acute myeloid leukemia (AML) [11]. Similar results were obtained by Ismail et al in childhood AML and acute lymphoblastic leukemia (ALL) [12]. Abe et al [13] found lower expression of BIRC6 in bone marrow-derived cells of healthy donors compared to de novo AML samples.…”
Section: Introductionmentioning
confidence: 70%
“…In their work, they pointed out the possible predictive meaning of the BIRC6 gene [27]. Furthermore, they suggest that BIRC6 gene expression may be recognized as a risk factor in children with acute leukemia [12]. Abe et al also revealed a much higher mRNA BIRC6 expression in marrow cells with MDS, in comparison to normal cells.…”
Section: Resultsmentioning
confidence: 98%
“…The risk factor and prognosis of patients with normal karyotype are analyzed by the abnormality of gene expression and molecular genetics change to direct the clinical individualized treatment, which has been a novel research direction for the leukemia treatment [12][13][14]. Meanwhile, the mutations of IDH2, ASXL1, and DNMT3A, which are closely related to the occurrence and development of acute leukemia, have attracted wide attention.…”
Section: Discussionmentioning
confidence: 99%